Palladium-Catalyzed Alkoxycarbonylation of Conjugated Enyne Oxiranes: a Diastereoselective Method for the Synthesis of 7-Hydroxy - Kuş, Melih; Artok, Levent; Kuş, Melih; Aygün, Muhittin; Artok, Levent (American Chemical Society, 2015)
Palladium-catalyzed alkoxycarbonylative 1,5-substitution of conjugated enyne oxiranes provides a diastereoselective route to (E)-configured 7-hydroxy-2,3,5-trienoates. The reactions proceeded in a highly stereoselective manner, possibly through sequential formation of π-allylpalladium and σ-vinylallenyl palladium complexes. The major diastereomeric form of the product is determined by the configuration of the alkenyl moiety of the substrate.
Keywords: Catalysis; Palladium compounds; Stereoselectivity; Alkoxycarbonylation; Diastereoselective